Optimization of Empirical Modelling of Advanced Highly Strained In0.7Ga0.3As/In0.52Al0.48As pHEMTs for Low Noise Amplifier - W.M. Jubadi; F. Packeer; M. Missous (International Journal of Electrical and Computer Engineering (IJECE), 2017)
An optimized empirical modelling for a 0.25µm gate length of highly strained channel of an InP-based pseudomorphic high electron mobility transistor (pHEMT) using InGaAs–InAlAs material systems is presented. An accurate procedure for extraction is described and tested using the pHEMT measured dataset of I-V characteristics and related multi-bias s-parameters over 20GHz frequency range. The extraction of linear and nonlinear parameters from the small signal and large signal pHEMT equivalent model are performed in ADS. The optimized DC and S-parameter model for the pHEMT device provides a basis for active device selection in the MMIC low noise amplifier circuit designs.